Limitations of How We Categorize People - Wallat, Cynthia; Steele, Carolyn (Education Policy Analysis Archives, 1999)
Social policy researchers and policy rules and regulation writers have not taken advantage of advances in assessing ways in which social representations of ideas about people can convey alternative explanations of social life. During the past decade a growing number of scholars have considered how representational practices and the representations that are outcomes of such practices have value. Neglecting to consider representational practices has consequences including failure to mobilize and sustain alternative ideologies that reject narrow perspectives on families and communities. As evidenced by recent OMB rulings on census categories, the dominant sense of meaning of population—and hence family and community—is quite similar to the 17th century sense of people as objects of a particular category in a place from which samples can be taken for statistical measurement. However, the contrastive analysis presented in this paper points out how sustained attention to consequences of use of sets of information categories collected to enumerate population to inform social policy can still materialize. In the wake of federal welfare reform, policy makers are particularly interested in questions of benefit relative to social service delivery and community revitalization. The presentation includes lessons learned from several dozen family, youth, school and community research projects.